(untitled) (Philological Studies, 2023)
Carevna Miladinova-Aleksieva was a teacher and writer who holds a significant place in Macedonian literary and cultural history of the second half of the 19th and the beginning of the 20th century. This article analyzes her recollections of the Ilinden Uprising (1903) recorded in two texts that were included in the book Epoch, Land and People, which was edited and posthumously published by her son Vladislav Alexiev. These documents are very interesting because they represent a personal, subjective view of one of the most notable events in Macedonian history, as well as the author’s experience as a contemporary of the events. They contain her memories conveyed with a degree of dramatic intensity and expressed with a lot of emotions. These chronicles do not insist on any strict factography, and even contain certain inaccuracies in that regard. Thus, the author depicts the atmosphere in the city of Bitola, where she resides in the period before and during the uprising, and speaks enthusiastically about the courage and sacrifice of both the insurgents and the people, as well as about the mass involvement in the uprising and the determination of the common people to fight for their freedom at the cost of their own lives. Despite the devastating consequences of the suppressed uprising, she emphasizes the indomitability of the people’s spirit and expresses her desire for Ilinden 1903 to never be forgotten.